ANALISIS ENERGI DAN BIAYA OPERASI BAHAN BAKAR METANOL PADA KAPAL OIL CHEMICAL TANKER 4000 DWT - Abyan Ariaputra Aziz (2023)
The International Maritime Organization (IMO) has introduced regulations that the shipping industry must reduce Greenhouse Gas Emissions by at least 50% by 2050 compared to 2008. At the same time, IMO predicts that shipping emissions in the world will increase by 250% by 2050. Therefore, the shipping industry needs to fix this problem by reducing carbon emissions. The selection of Methanol Fuel on ships is an alternative fuel for ships that is cost-effective, low emission, environmentally friendly, and renewable. Methanol can reduce SOx emissions by up to 99%, NOx emissions by up to 60%, and Particular Matters by up to 95%. The purpose of this study is to analyze the availability of Methanol fuel in the shipping world associated with safety regulations for Methanol-fueled ships, make adjustments to the main methanol-fueled engine, calculate energy and operating costs on 4000 DWT Oil Chemical Tanker ships with the One Trip Voyage method with Route Variations, Composition, and Fuel Cost. From the discussion of this study, it can be concluded that the results of energy calculations, operating costs, and retrofit prices on the 4000 DWT Oil Chemical Tanker ship with American route shipping amounted to 3,467,320 MJ, Rp. 1,565,684,341. -, and 2.4-years payback period, European routes amounted to 3,137,099 MJ, Rp. 1,352,844,897. -, and 2.8-years payback period, and Asia Pacific routes amounting to 3,274,914 MJ, Rp. 1,069,629,506. -, and 3.5-years payback period, as well as the main engine retrofit price reaching Rp. 7,574,435,035.-.